The Effectiveness of Consumption of Red Guava Juice Against Increasing Hemoglobin Levels in Pregnant Women - Wiwin Purwini; Rahayu Khairiah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: To evaluate the effectiveness of consuming red guava juice on increasing hemoglobin levels in pregnant women. Methods: Quasi-experimental with Pretest Posttest With Control Group Design. The sample in this study were all 38 pregnant women who experienced anaemia from January to March 2022, and the sampling technique was total sampling. Results: The average HB level in the intervention group pretest was 10.24gr%, and the post-test was 12.49gr%. In the control group, the pretest was 10.32gr%, and the post-test was 10.96gr%. There is an effect of consuming red guava juice in increasing haemoglobin levels in pregnant women with a p-value of 0.000. Conclusion: There is effectiveness of consuming red guava juice in increasing hemoglobin levels in pregnant women. It is expected that midwives provide input in efforts to improve health services to pregnant women to advise pregnant women to consume red guava juice to prevent anemia.